2020
DOI: 10.3389/fnut.2020.00126
|View full text |Cite|
|
Sign up to set email alerts
|

Seed Composition and Amino Acid Profiles for Quinoa Grown in Washington State

Abstract: Quinoa (Chenopodium quinoa Willd.) is a pseudocereal celebrated for its excellent nutritional quality and potential to improve global food security, especially in marginal environments. However, minimal information is available on how genotype influences seed composition, and thus, nutritional quality. This study aimed to provide a baseline for nutritional quality of Washington grown quinoa and test the hypothesis that these samples contain adequate amounts of essential amino acids to meet daily requirements s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 77 publications
(155 reference statements)
3
37
0
Order By: Relevance
“…It has been hypothesized that protein and amino acids contents can be determined by nitrogen availability in the soil, the environmental and agroecological conditions, and the genotype (Thanapornpoonpong et al, 2008;Craine and Murphy, 2020). In this study, a significant variability throughout samples was found in both protein and amino acid contents (Figure 5 and Table 1).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…It has been hypothesized that protein and amino acids contents can be determined by nitrogen availability in the soil, the environmental and agroecological conditions, and the genotype (Thanapornpoonpong et al, 2008;Craine and Murphy, 2020). In this study, a significant variability throughout samples was found in both protein and amino acid contents (Figure 5 and Table 1).…”
Section: Discussionmentioning
confidence: 59%
“…harvested in 2018 met the daily children and adults' recommendations, especially due to the low levels of methionine (Table 1). Both methionine and tryptophan may be limiting in quinoa (Mahoney et al, 1975;Gonzalez et al, 2012;Craine and Murphy, 2020). Therefore, overall, and based on these and previous analysis (Craine and Murphy, 2020), increased lysine and sulfur amino acids levels should be breeding targets in quinoa toward enhancing quality to reach Food Security.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Quinoa seeds are highly nutritious, containing high contents of fiber, vitamins such as ascorbic acid, alpha-tocopherol, thiamin, and riboflavin, and minerals. Quinoa protein quality is high as it contains the nine essential amino acids in significant amounts, though not always in sufficient quantities to be a complete protein source to consumers across all age groups [11]. Moreover, quinoa possesses phytochemicals such as phenolics and bioactive peptides; these components have demonstrated beneficial effects on metabolic, cardiovascular, and gastrointestinal health [12][13][14].…”
Section: Introductionmentioning
confidence: 99%